Promotional effect of Ti doping on the ketonization of acetic acid over a CeO2 catalyst. Issue 36 (19th April 2017) - Lu, Feipeng; Jiang, BinBo; Wang, Jingdai; Huang, Zhengliang; Liao, Zuwei; Yang, Yongrong; Zheng, Jie
Abstract : The promotional effect of Ti doping on the ketonization of acetic acid over a CeO2 catalyst was investigated. Abstract : A series of Ce1− x Ti x O2− δ mixed oxide catalysts were synthesized using a homogeneous precipitation method and characterized, and then these catalysts were applied to convert acetic acid to acetone using a gas-phase ketonization reaction. Ti-doped Ce1− x Ti x O2− δ catalysts ( x = 0.1–0.5) exhibited much better ketonization performance than their parent catalysts of CeO2 and TiO2, and such Ti-doping-induced catalysis improvement is attributed to the formation of a Ce–O–Ti structure depending on the Ti content. Among the different Ce1− x Ti x O2− δ catalysts, the Ce0.7 Ti0.3 O2− δ catalyst calcinated at 500 °C showed the best catalysis activity and high stability. A combination of techniques ( i.e. TEM, FTIR, H2 -TPR, NH3 /CO2 -TPD and XPS) further revealed that the formation of the Ce–O–Ti structure modified the surface acid–base properties and thus enhanced the redox properties. Moreover, the introduction of Ti into CeO2 also increased the number of oxygen vacancies on the catalysts' surface that favored the ketonization of acid molecules. This work provides valuable insights into the design of highly efficient CeO2 -based catalysts for acid removal in the upgrading process of bio-oil.